Bearing failure and strengthening mechanism of countersunk thin-ply laminated joints using an interference-fit bolt - Anyang Wang; Zhongqi Wang; Menglin Zhao; Yang Zhao; Xingchen Men; Zhengping Chang; Yonggang Kang (Polymer Testing, 2024)
By experimentation, this study investigated interference-fit effects on the bearing failure of thin-ply composite countersunk single-lap joints. A comparative study of the mechanical behaviour and strengthening of the bolt-hole wall during the assembly of thin-ply and thick-ply specimens with varying interference sizes has been carried out. The effect of the interference-fit on the strength of countersunk composite bolted joints with thin-ply has been studied in detail under quasi-static tensile loading. The interface strengthening and failure mechanisms of thin-ply interference joints were characterized by means of SEM micrographs. Thin-ply laminates exhibited lower installation forces during assembly. The use of thin-ply in the interference joints' area could still demonstrate suppression of the damage's generation and propagation. More importantly, thin-ply laminates could accommodate larger interference sizes than thick-ply laminates and have higher load-bearing capacities, approximately 10%–20 % higher. Thin prepregs could be used to facilitate the design process and improve composites' structural properties, providing new perspectives for improvements and innovative applications of interference joining technology. The results of this study have some guidance for the aerospace application of thin prepregs in thin-walled structures.